2004
DOI: 10.1590/s1806-37132004000800002
|View full text |Cite
|
Sign up to set email alerts
|

Diretrizes para Cessação do Tabagismo

Abstract: Autores e colaboradores Diretrizes para Cessação do Tabagismo Número de substâncias identificadas em 15 funções químicas existentes no fumo Funções Número de químicas substâncias Amidas, imidas 237 Ácidos carboxílicos 227 Lactonas 150 Ésteres 474 Aldeídos 108 Cetonas 521 Álcoois 379 Fenóis 282 Aminas 196 N-eterocíclicos 921 Hidrocarbonetos 755 Nitrilas 106 Éteres 311 Carboidratos 42 Anidridos 11 Total 4.720

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
5
48

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 21 publications
(28 reference statements)
0
23
5
48
Order By: Relevance
“…This study's results provide an important contribution to the literature on smoking in Brazil, where studies on smoking cessation are still scarce 6 . Most of the existing articles deal with smoking initiation and the factors and harm associated with tobacco use 2,23,24,28 . In addition, as mentioned above, no similar Brazilian study was found with a nationwide scope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study's results provide an important contribution to the literature on smoking in Brazil, where studies on smoking cessation are still scarce 6 . Most of the existing articles deal with smoking initiation and the factors and harm associated with tobacco use 2,23,24,28 . In addition, as mentioned above, no similar Brazilian study was found with a nationwide scope.…”
Section: Discussionmentioning
confidence: 99%
“…With nicotine as the main psychoactive component of tobacco, smoking shows the highest addiction rate among legal and illicit drugs 2 and is further identified as the leading cause of avoidable mortality, causing some 6 million deaths every year and huge damage to the world economy. If the current trend continues, by 2030 smoking will cause an estimated 8 million deaths per year in the world 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering gender, 21.6% of Brazilian men and 13.1% of women are smokers (5) . An estimated 200,000 deaths related to smoking occur annually (1) and, in the more economically developed cities, the prevalence of smoking among women is now close to that observed among men. This indicates an increasing trend of tobacco exposure in females, probably the result of strong advertising aimed specifically at this population group (3) .…”
Section: Introductionmentioning
confidence: 98%
“…report that smoking one cigarette increases the heart rate to 10-20 beats per minute, returning to baseline values after 15-45 minutes after ceasing smoking. However, other substances present in cigarettes have harmful effects on the body; -benzopyrene is considered the most carcinogenic 3,4 .…”
Section: Introductionmentioning
confidence: 99%